The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/ijerph191610305
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Exposure to Fine Particulate Matter and the Risk of Chronic Liver Diseases: A Meta-Analysis of Observational Studies

Abstract: Although fine particulate matter (PM2.5) is a known carcinogen, evidence of the association between PM2.5 and chronic liver disease is controversial. In the present meta-analysis study, we reviewed epidemiological studies to strengthen evidence for the association between PM2.5 and chronic liver disease. We searched three online databases from 1990 up to 2022. The random-effect model was applied for detection of overall risk estimates. Sixteen eligible studies, including one cross-sectional study, one retrospe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 67 publications
0
7
0
Order By: Relevance
“…The liver is an active organ central to metabolism and detoxification for exogenous chemicals. Many research studies indicate that PM 2.5 has toxic effects on the liver [7,8], including triggering liver cancer and NAFLD. The toxicological mechanisms involve liver pathology injury, inflammation, oxidative stress, liver fibrosis and abnormal lipid metabolism induced by prolonged exposure to PM 2.5 [4,6,21].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The liver is an active organ central to metabolism and detoxification for exogenous chemicals. Many research studies indicate that PM 2.5 has toxic effects on the liver [7,8], including triggering liver cancer and NAFLD. The toxicological mechanisms involve liver pathology injury, inflammation, oxidative stress, liver fibrosis and abnormal lipid metabolism induced by prolonged exposure to PM 2.5 [4,6,21].…”
Section: Discussionmentioning
confidence: 99%
“…Empirical research has revealed that PM 2.5 infiltrates the liver via the bloodstream, instigating a cascade of pathological alterations, including hepatic inflammation, oxidative stress, steatosis, and liver fibrosis [4][5][6], exerting profound impacts on liver function. A meta-analysis indicated that long-term exposure to PM 2.5 was associated with an increased risk of chronic liver disease [7]. Studies have also pointed to a significant relationship between exposure to PM 2.5 and the incidence of non-alcoholic fatty liver disease (NAFLD) [8].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that air pollution is associated with an increased risk of chronic liver disease [82][83][84]. In a cross-sectional study involving 90,086 participants, Guo et al found that when the 3-year average concentrations of PM 1 , PM 2.5 , PM 10 , and NO 2 increased by 10 µg/m 3 , the risk of metabolic dysfunction-associated fatty liver disease (MAFLD) increased by 13% (95% CI: 10-17%), 29% (1.25-1.34%), 11% (9-14%), and 15% (12-17%), respectively [82].…”
Section: Metabolic Dysfunction Diseasesmentioning
confidence: 99%
“…In a cross-sectional study involving 90,086 participants, Guo et al found that when the 3-year average concentrations of PM 1 , PM 2.5 , PM 10 , and NO 2 increased by 10 µg/m 3 , the risk of metabolic dysfunction-associated fatty liver disease (MAFLD) increased by 13% (95% CI: 10-17%), 29% (1.25-1.34%), 11% (9-14%), and 15% (12-17%), respectively [82]. A meta-analysis of 16 studies showed that when PM 2.5 increased by 10 µg/m 3 , the risk of liver cancer, liver cirrhosis, and fatty liver disease increased by 23 (95% CI: 14-33%), 17 (6-29%), and 51% (9-108%), respectively [84]. The increased risk of these diseases suggests that air pollution may lead to abnormal liver lipid metabolism, which has also been confirmed in some animal experiments [85][86][87].…”
Section: Metabolic Dysfunction Diseasesmentioning
confidence: 99%
“…We evaluated the quality of eligible literature works and scored all publications from 0 to 9 on the Newcastle-Ottawa Scale (NOS) [23]. Studies awarded higher scores than the mean score were considered as high-quality studies.…”
Section: Literature Quality Assessmentmentioning
confidence: 99%